Kulturotechnika jako forma oddziaływań korekcyjno-terapeutycznych wśród osadzonych = Cultural education as a form of corrective and therapeutic interaction among convicts - Toroń-Fórmanek, Barbara (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Socially maladjusted people, who have difficulties in creating, fulfilling and filling the roles determined by the society with new identity content, have impoverished, socially unaccepted, and fragmentary personalities. Having such a so-called negative identity means that the person constantly creates their own personality and it is never set permanently.
Keywords: tożsamość negatywna; twórcza resocjalizacja; kulturotechnika; readaptacja; negative identity; creative rehabilitation; cultural education; readaptation